Eu:CROPIS AIV Program: Challenges and Solutions for a Spin-Stabilized Satellite Containing Biology - Toni Delovski; Catherin Düvel; Fabian Greif; Ansgar Heidecker; Sebastian Kottmeier; Olaf Mierheim; Falk Nohka; Fabian Orlowski-Feldhusen (International Journal of Aerospace Engineering)
Eu:CROPIS is DLR’s first mission of the Compact Satellite Program. Its primary payload focuses on the research of closed-loop biological, regenerative life support systems, in a simulated gravitational environment of the Moon and Mars over months at a time. This is achieved by rotation of the satellite around its central body axis, using only magnetic torquers as actuators. A secondary payload (“PowerCells”) by the NASA Ames Research Center also utilizes the artificial gravity to conduct growth experiments on genetically modified organisms (GMOs). These payloads and the system design imposed constraints which affected the Assembly Integration and Verification (AIV) program in various ways and created challenges for the relatively small team to find solutions for. The paper to be presented will address the different aspects of the AIV program. This includes the verification of different critical components like the newly developed CFRP pressure vessel containing the primary payload and the Micrometeoroid and Debris Protection Shield, which protects it. Both items went through rigorous testing, including high-velocity impact tests, to ensure their reliability in orbit. Various other aspects concerning the biology had to be taken into account during AIV campaigns: due to the presence of degradable components within the primary payload, a late access capability had to be implemented in order to exchange biology as well as chemistry in cases of launch delays. To allow these operations as close as six months prior to launch, a highly flexible and streamlined acceptance test campaign was developed. A major impact on test planning and logistics was the fact that the secondary payload “PowerCells” contains GMOs, which European and German regulations restrict to be handled exclusively in especially certified laboratories (biosafety level 1 (BSL-1)). Thus, the use of external test facilities for the flight model campaign was not feasible as no European test center is certified to BSL-1. In consequence, the clean room facilities of the DLR Institute of Space Systems had to be certified to BSL-1 and new test infrastructure had to be procured in a short time frame to cover for acceptance testing. The design of the satellite and nature of the attitude control subsystem required limits on the magnetic momentum of the system and every unit it contains. A test flow incorporating the magnetic property measurement of each unit and a final system-level test in an external facility had to be devised, which enabled budgeting and projection of expected measurement results on the system level. Furthermore, the moments of inertia had to be measured precisely in order to have a stable spinning axis enabling a stable gravity simulation. Finally, the functionality had to be verified for each unit and for the system which required that several small test campaigns had to be conducted, like a solar panel deployment test and extensive software testing. A tight link to the operations teams of the German Space Operations and Control Center during such tests and beyond finally ensures the operability of the overall system in the operational phase.